Fatal Cardiac Tamponade following Rupture of Saccular Aneurysm of Ascending Aorta: A Case Report - Singh, Kh Pradipkumar; Meera, Th; Devi , Ph Madhubala (Journal of Indian Academy of Forensic Medicine, 2014)
Thoracic aortic aneurysms often go unnoticed as the patients rarely feel any symptoms. There have been many instances where a healthy person without any significant history of illness was found dead at home or at work place and such cases always raise a suspicion of foul play. A 40-year old man was found unconscious on the bank of a river and he was immediately taken to the hospital; however, he was declared brought dead on arrival. Foul play was suspected and his body was brought for autopsy at the Regional Institute of Medical Sciences, Imphal. On examination, massive haemopericardium along with an external rupture of a saccular aneurysm of the ascending aorta was observed. Aortic aneurysm is associated with significant mortality that mandates early identification and management. In India, routine health screening is prevalent only amongst the affluent class. Hence, health screening of the general population is recommended so as to avert such fatal outcomes and at the same time, it would help in reducing needless litigations.